Fungsi Kitchen Equipment and Utensils Dalam Menunjang Operasional Hot Kitchen Di Grandkemang Hotel Jakarta - Martinus Hia; Donant Alananto Iskandar (Research and Community Service UNIVERSITAS KALBIS, 2025)
This study aims to analyze the function of Kitchen equipment and Kitchen utensils in supporting hot Kitchen operations at Grandkemang Hotel Jakarta. The development of the tourism industry requires hotels to provide high-quality food and beverage services; therefore, the availability and proper utilization of Kitchen equipment are important factors in supporting the food production process. This research employs a descriptive qualitative method, with data collected through direct observation and interviews with Kitchen staff. The findings indicate that adequate and well-functioning Kitchen equipment and Kitchen utensils play a significant role in improving work efficiency, maintaining consistency in food quality, and supporting coordination among Kitchen sections. Furthermore, systematic Kitchen equipment management contributes to the smooth operation of the hot Kitchen and enhances the overall quality of hotel services.